Foreign Bank Subsidiaries' Default Risk during the Global Crisis : What Factors Help Insulate Affiliates from their Parents? - Anginer, Deniz; Cerutti, Eugenio; Martinez Peria, Maria (Washington, D.C. : International Monetary Fund, 2016)
This paper examines the association between the default risk of foreign bank subsidiaries in developing countries and their parents during the global financial crisis, with the purpose of determining the size and sign of this correlation and, more importantly, understanding what factors can help insulate affiliates from their parents. We find evidence of a significant and robust positive correlation between parent banks' and foreign subsidiaries' default risk. This correlation is lower for subsidiaries that have a higher share of retail deposit funding and that are more independently managed from their parents. Host country bank regulations also influence the extent to which shocks to the parents affect the subsidiaries' default risk. In particular, the correlation between the default risk of subsidiaries and their parents is lower for subsidiaries operating in countries that impose higher capital, reserve, provisioning, and disclosure requirements, and tougher restrictions on bank activities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet